2012
DOI: 10.1182/blood-2011-06-364182
|View full text |Cite
|
Sign up to set email alerts
|

A clinically relevant population of leukemic CD34+CD38− cells in acute myeloid leukemia

Abstract: Relapse of acute myeloid leukemia (AML

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
191
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(205 citation statements)
references
References 37 publications
11
191
1
2
Order By: Relevance
“…These challenges may result from residual cancer stem cells, which may be resistant to conventional chemo-and radiotherapies and are therefore difficult to eradicate. Gerber et al demonstrated, for the first time, that the presence of CSCs in AML correlates with a poor clinical outcome and suggested that those cells may be responsible for tumor relapse [40]. Therefore, these cells could be responsible for the selection of drug-resistant clones and the eventual development of multidrug resistance (Fig.…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%
“…These challenges may result from residual cancer stem cells, which may be resistant to conventional chemo-and radiotherapies and are therefore difficult to eradicate. Gerber et al demonstrated, for the first time, that the presence of CSCs in AML correlates with a poor clinical outcome and suggested that those cells may be responsible for tumor relapse [40]. Therefore, these cells could be responsible for the selection of drug-resistant clones and the eventual development of multidrug resistance (Fig.…”
Section: Cancer Stem Cells-past and Currentmentioning
confidence: 99%
“…In both normal BM and in the majority of AML BM cells, the CD34+/CD38−/ALDH high population is considered to contain only HSC [21,29,30]. In contrast to normal BM, in AML a second population can be discriminated with cells having intermediate ALDH expression [29]. When purified, this population was most potent in AML engraftment in immunodeficient mice and was generally found positive for leukemic cytogenetic markers [29].…”
Section: Identification Of Leukemic Stem Cellsmentioning
confidence: 99%
“…In normal BM CD34+/CD38− HSC display high levels ALDH activity (ALDH high ) [29]. In both normal BM and in the majority of AML BM cells, the CD34+/CD38−/ALDH high population is considered to contain only HSC [21,29,30]. In contrast to normal BM, in AML a second population can be discriminated with cells having intermediate ALDH expression [29].…”
Section: Identification Of Leukemic Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Higher LPC frequencies and a gene expression profile typical of LPCs at diagnosis are predictive of unfavorable clinical outcomes in AML. [9][10][11][12] Recently, we reported that LPCs in Ph + ALL are enriched in the CD34 + CD38 − CD58 − fraction using an anti-CD122-conditioned NOD/SCID xenograft assay by intra-BM injection. Moreover, our preliminary data indicate that a CD34 + CD38 − CD58 − LPC phenotype at diagnosis is an independent risk factor for relapse in a cohort of 63 patients with de novo Ph + ALL.…”
Section: Introductionmentioning
confidence: 99%